Future of the media : sights from the inside - Leppänen, Mikko (2012)
Journalists as workers and makers of news are a very important stakeholder group for news media companies. It is vital for organizations to acknowledge the needs and expectations of their stakeholders, because fulfilled expectations lead to stakeholder favor and good organizational reputation. Unmet expectations lead to loss of stakeholder trust and bad organizational reputation.